2016
DOI: 10.1186/s12889-016-3074-1
|View full text |Cite
|
Sign up to set email alerts
|

Substantial improvements not seen in health behaviors following corner store conversions in two Latino food swamps

Abstract: BackgroundThe effectiveness of food retail interventions is largely undetermined, yet substantial investments have been made to improve access to healthy foods in food deserts and swamps via grocery and corner store interventions. This study evaluated the effects of corner store conversions in East Los Angeles and Boyle Heights, California on perceived accessibility of healthy foods, perceptions of corner stores, store patronage, food purchasing, and eating behaviors.MethodsHousehold data (n = 1686) were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 24 publications
2
57
1
Order By: Relevance
“…It will be interesting to see if proactive food retailers will lead the way in making store environments more supportive of healthy choices. The public health literature suggests that consumer pressure, public policy and ambitious public-private partnerships are needed to push for substantial and sustainable changes in the food retail environment [17, 18, 55]. …”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to see if proactive food retailers will lead the way in making store environments more supportive of healthy choices. The public health literature suggests that consumer pressure, public policy and ambitious public-private partnerships are needed to push for substantial and sustainable changes in the food retail environment [17, 18, 55]. …”
Section: Discussionmentioning
confidence: 99%
“…Other farmers' market studies analyse self-reported use of government incentive programs, government incentive sales data or records of coupon redemption [61][62][63][64][65][66], self-reported amounts spent [67] or total sales [39]. Some studies on convenience stores use purchase data collected using these same methods [68][69][70][71][72][73][74][75]. Given technological advances and changing legal requirements [76] in tracking sales, point of sales (POS) terminals are starting to gain popularity in UPS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the data used in this study is relatively old (2000–2002), with data available at the census tract-level only. We cannot discard the possibility of different results if we had access to more current data, especially since some improvements in the food environment have taken place in Los Angeles since 2000–2002 [31], and/or data on smaller geographies. Furthermore, we did not account for population density, which may have confounded our results.…”
Section: Discussionmentioning
confidence: 99%